Maternal Mental Health and Stunting among Children Aged 24-59 Months in Jember Regency - Sari, Firli Riana; Susanto, Tantut; Susumaningrum, Latifa Aini (Jember Maternal and Child Health Journal, 2026)
Background: Stunting remains a major nutritional problem worldwide, especially in midlle and low-income countries.Poor mental health may diminish a mother’s capacity to adequately care for her child, which will ultimately contribute to stunting in children. Aim: The aim of this study was to analyze the relationship between maternal mental health and stunting among children aged 24–59 months in Jember District. A Cross-Sectional study was conducted among 215 mothers who had children in the age group of 24–59 months using stratified random sampling. A self-administered questionnaire was used to collect the data, including socio-demographic data and a self-reporting questionnaire (SRQ-20), while digital microcode and digital scales were used to measure children's anthropometry. Result: The result showed that 44% of mothers were identified as having indicated mental health disorders. Meanwhile, children who suffer from stunting were 76% and 24% classified as severely stunted. The results of research using the Chi-Square test showed that maternal mental health was significantly associated with stunting ((χ2= 4,44; p-value <0,05). Moreover, maternal mental health is a protective factor against more severe stunting in children (OR= <1; 95% CI= 0.278-0.959). Conclusions: Maternal mental health is a associated with stunting among children in the age group of 24–59 months.Therefore, emphasis should be given to preventing, managing, and maintaining maternal mental health to prevent stunting.